Investigation of noise dispersion from seaport equipment on the enterprise territory and residential environment - Baltrėnas, Pranas; Fröhner, Klaus-Dieter; Puzinas, Dainius (Journal of Environmental Engineering and Landscape Management, 2007)
The level of noise and its dispersion was evaluated at Klaipeda State Seaport Joint Stock Company (JSC) KLASCO. Investigation was carried out at 24 measuring points located on the enterprise territory and at 6 measuring points in a residential environment. Sources of noise were evaluated. The work was focussed on the reasons of a higher noise level than that presented in the hygiene norms and on possible reasons of its occurance on the territory of the enterprise and on the nearby residential territory. Noise decreasing means are suggested. The investigation results are presented as noise distribution isolines.Article in Lithuanian.Jūrų uosto įrenginių triukšmo sklaidos įmonės ir gyvenamojoje teritorijoje tyrimaiSantrauka. Įvertinamas triukšmo lygis ir jo sklaida Klaipėdos valstybinio jūrų uosto kompanijoje AB KLASCO. Tyrimai atlikti 24 matavimo vietų, išdėstytų zonomis, įmonės teritorijoje ir 6 matavimo vietose gyvenamojoje aplinkoje, atlikti ekvivalentinio triukšmo tyrimai. Siekta įvertinti triukšmo šaltinius, higienos normų viršijimus ir jų galimas priežastis įmonės gamybinėje teritorijoje ir šalia jos gyvenamojoje teritorijoje, nustatyti įmonės skleidžiamą triukšmą ir parengti priemones jam mažinti. Rezultatai pateikiami triukšmo sklaidos pasiskirstymo izolinijomis.Reikšminiai žodžiai: triukšmo tyrimai, ekvivalentinis triukšmas, higienos normos.Исследование распространения шума, исходящего из сооружений морского порта, на территории предприятия и жилой зоныРезюме. Представлена оценка уровня шума, а также его распространение на предприятии Клайпедского государственного морского порта АО „КЛАСКО“. Исследование шума производилось в 24 местах, расположенных по зонам на территории предприятия и в 6 местах на территории жилой зоны. Целью исследования было определить главные источники шума; установить превышение его величины по сравнению с гигиеническими нормами, возможные причины шума на территории промышленного предприятия и возле него на территории жилой зоны; виды шумов, которые распространяет производство, a также предложить меры по их уменьшению. Результаты исследования распространения шума представлены в форме изолиний.Ключевые слова: исследование шумa, эквивалентный шум, гигиенические нормы.First Published Online: 14 Oct 2010